The changes of rhizosphere microbial communities in pepper varieties with different capsaicinoids - Li, Xin; Zhang, Yan; Zhou, Chi; Li, Xuefeng; Zou, Xuexiao; Ou, Lijun; Tao, Yu (Frontiers in Microbiology, 2024)
Capsaicinoids are produced uniquely in pepper fruits, and its level determines the commercial quality and health-promoting properties of pepper. So, it is particularly important to increase capsaicinoids content in pepper. Rhizosphere microbiota is critical to plant growth and performance, and affected by plant varieties. However, the impact of pepper varieties with different capsaicinoids yields on the rhizosphere microbiota is poorly understood. Using high-throughput sequencing of the 16S rRNA and internal transcribed spacer (ITS) region, we investigated the rhizosphere microbial community among five pepper varieties containing different capsaicinoids. Our results demonstrated that pepper variety significantly influenced the diversity and structure of rhizosphere microbial community. Bacterial diversity in varieties with high capsaicinoids content was significantly higher than in varieties with low capsaicinoids content, while fungal diversity was opposite to bacterial diversity. while fungi was contrary to bacteria. The correlation analysis revealed that nineteen dominant bacterial genera (e.g., Chujaibacter, Rhodanobacter and Gemmatimonas) were significantly correlated with capsaicinoids content, and nine of them were also significantly associated with soil nutrients, whereas only one fungal genus (Podospora) was significantly correlated with capsaicinoids content. Additionally, almost all genera which significantly correlated to capsaicinoids content were biomarkers of the five pepper varieties and the correlation was well corresponding to the capsaicinoids content. Overall, our results confirmed that the variety of pepper significantly affected the rhizosphere microbial community in the fields, and bacteria and fungi responded differently to capsaicinoids, which may affect the biosynthesis of capsaicinoids and contribute to further improvement of capsaicinoids production in pepper fruits.